Crime, fear of crime and mental health: synthesis of theory and systematic reviews of interventions and qualitative evidence - Theo Lorenc; Mark Petticrew; Margaret Whitehead; David Neary; Stephen Clayton; Kath Wright; Hilary Thomson; Steven Cummins; Amanda Sowden; Adrian Renton (NIHR Journals Library, 2014)
Background: Crime and fear of crime may impact negatively on health and well-being. Interventions to reduce crime and fear of crime, particularly interventions in the physical environment, may be a promising way to improve population-level well-being. Project components: (1) Mapping review of theories and pathways; (2) systematic review of effectiveness; (3) systematic review of UK qualitative data; and (4) focus groups and interviews with stakeholders. Methods: (1) The mapping review was a pragmatic non-systematic review focusing on theoretical literature and observational quantitative studies and development of a theoretical model of pathways. (2 and 3) The systematic reviews followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance. In total, 18 databases including EMBASE, MEDLINE, PsycINFO and Science Citation Index were searched from inception to 2010. Studies presenting data on the built environment and the fear of crime were included. Quality assessment was conducted. Data synthesis was conducted narratively for the intervention review, with harvest plots to synthesise data on inequalities, and by thematic analysis for the review of qualitative evidence. (4) Semistructured interviews with nine stakeholders working in community safety and two focus groups with members of the public were conducted to inform the methods of the project and the dissemination of findings. Data were analysed thematically. Results: (1) There are complex and often indirect links between crime, fear of crime, environment, and health and well-being at both individual and population levels. Fear of crime is associated with poorer health outcomes. There is considerable debate about the measurement of fear of crime. Both fear of crime and crime are associated with a range of environmental factors. (2) A total of 12,093 references were screened on abstract for the two systematic reviews. Of these, 47 effectiveness studies (22 controlled and 25 uncontrolled) were included in the systematic review of effectiveness, with 36 conducted in the UK, 10 in the USA and one in the Netherlands. There is some evidence that home security improvements and non-crime-related environmental improvements may improve some fear of crime outcomes. There is little evidence that the following reduce fear of crime: street lighting improvements, closed-circuit television, multicomponent environmental crime prevention programmes or regeneration programmes. The evidence on housing improvement is mixed. Very few data on the health and well-being outcomes of crime reduction interventions were located and the study quality overall is poor. (3) A total of 39 studies were included in the systematic review of qualitative data. Several factors in the physical environment are perceived to impact on fear of crime. However, factors in the local social environment appear to be more important as drivers of fear of crime. There is considerable evidence for limitations on physical activity as a result of fear of crime, but less for mental health impacts. (4) Stakeholders see fear of crime as harder to address than crime and as linked to health and well-being. Environmental interventions, such as Secured by Design, are widely used and positively regarded. Limitations: The review is relatively restricted in its scope and a number of relevant interventions and themes are excluded. The underlying evidence base is of limited quality, particularly for the effectiveness review, and is heterogeneous. Conclusions: Broader social interventions appear more promising than crime-focused environmental interventions as a means of improving fear of crime, health and well-being. The qualitative evidence suggests that fear of crime may impact on physical activity. More broadly, crime and fear of crime appear to be linked to health and well-being mainly as aspects of socioeconomic disadvantage. This review indicates the following gaps in the literature: evaluation research on the health impacts of crime reduction interventions; more robust research on interventions to reduce fear of crime; systematic reviews of non-environmental interventions to reduce fear of crime and systematic reviews of qualitative evidence on other crime-related topics. Funding: The National Institute for Health Research Public Health Research programme.